The green competitiveness of Polish regions - Kasztelan, Armand (Zielona konkurencyjność polskich regionów, 2020)
Nowadays, environmental factors are seen as an important element in achieving competitive advantage at micro, meso and macro levels. The paper presents an assessment of the green competitiveness of Polish regions in the years 2004 and 2018 (last available data). For the purposes of the analysis, 25 indicators of the condition and protection of the environment and also environmental pressures were selected. Research was carried out based on the taxonomic linear ordering method, which enabled multidimensional comparative analysis (MCA). The adopted method made it possible to evaluate the studied phenomenon as a whole, providing grounds for assigning the Polish regions into four groups, characterized by a similar level of green competitiveness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 32-41
Keywords: competitiveness; environment; green growth; natural capital; taxonomic methods; konkurencyjność; środowisko; zielony wzrost; kapitał naturalny; metody taksonomiczne